Process automation in biotechnology engineering: reshaping and assessing active learning during disastrous events - Zavala-Yoé, Ricardo (Frontiers in Education, 2025)
Courses such as process automation (PA) can be difficult to grasp, even for engineering students. In addition to the inherent challenge of relating abstractions to real-life situations, we found that our students could not grasp basic concepts. After 5 years of work, we improved our students' performance in these fields. The solution involved redefining the course topics and closely monitoring their learning from the beginning of the course. The approach was enhanced with the support of specialized software and modifications to traditional active learning (AL) methods. Additionally, remote-mode AL was enabled by our institution in response to the 2017 earthquake and the 2019 pandemic. We investigated the difference δ = F−X between projects grades F and exams X via their medians. First, a test was applied to see whether the medians of δ were significantly different from 0. This result was true at 5% of level in 9 out of 12 classes, indicating improvement via F. Later, key groups 2015, 2017 and 2020 were similarly contrasted. Significant differences to zero were appreciated in groups 2015 vs. 2017, 2015 vs. 2020 (progress) but not in 2017 vs. 2020 may be due to those terrible events. Our novelty resulted statistically significant.